Few-group diffusion theory parameters from lattice calculations using leakage corrected collision probabilities. (15th September 2020) - Ray, Sherly; Degweker, S.B.; Kannan, Umasankari
Highlights: A new method to account for the leakage effect during lattice calculation is described. Flux distribution obtained is used to obtain the homogenised few-group cross sections and D . The methodology is used to obtain both axial and radial diffusion coefficients ( D ). Core k-effective by these cross sections and D is better than that by standard methods. Abstract: The paper describes a new method for lattice calculations for obtaining the leakage corrected neutron distribution and spectrum and few group diffusion theory parameters therefrom. The leakage correction is carried out, with the help of leakage corrected collision probabilities, during the lattice calculation of the heterogeneous medium and not after homogenisation following a lattice calculation. Expressions are derived for axial and radial leakage corrected collision probabilities using a method similar to the one used in an earlier paper for obtaining homogenised axial diffusion coefficients. These expressions have been coded in the LWR lattice code BOXER3 for calculation of the leakage corrected flux distribution and few group diffusion theory parameters. Comparisons of the results of core calculations using parameters obtained by the proposed method (i.e. using leakage corrected flux spectrum and distribution) and by standard P1 and B1 methods with Monte Carlo results are presented.